Design Simulation Program of Runway Capacity Using Genetic Algorithm At Soekarno-Hatta Airport - Saragih, Hoga; Wibowo, Indra Sulistyo; Utomo, Wisnu Darjono Tulodo (CommIT (Communication and Information Technology) Journal, 2011)
The purposes of this research are to calculate the capacity of runway with runway capacity simulation software using Genetic Algorithm, and to analyze the efforts which have more profound effect.The result of the hourly runway capacity with the mathematical calculation is 42 operations for arrival only, 110 operations for departure only and 64 operations for mix. To enhance the runway capacity, some strategies are researched, such as reduction of separation to meet criteria set by FAA’s rule, addition of the exit taxiway, addition of the runway according to master plan of Soekamo-Hatta Airport and changing the runway utilization strategies. Out of the four strategies, the most efficient solution is changing the runway utilization strategies (with capacity increase of 35,9 %) and reduction in separation (with capacity increase of 34,4 %). However, the addition of runway has the highest capacity increase, that is 53,9 %..Key Words: genetic algorithm, simulation, runway capacity.